Geographical Information Systems and Remote Sensing as Tools for Rural Development in Sub-Saharan Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Proceedings of a CTA-ITC seminarEnschede, The Netherlands, 23-26 September 1997. 262 pp. ISBN 92 9081 1986 CTA No 908, 40 credit points